Protective Effects of Short-Chain Fatty Acids on Gut Mucosa - Nurwiyeni Nurwiyeni; Aisyah Ellyanti; N Hilbertina; Almurdi Almurdi (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Background: Short-chain fatty acids (SCFAs) are key metabolites produced by microbial fibre fermentation and act as an epigenetic link between diet and gene expression. SCFA production is highly dependent on dietary fiber diversity to support a healthy microbial ecosystem. Through the gut-brain axis, SCFAs influence cognitive function by altering the brain's response to food signals and reducing systemic inflammation. Objective: This study aimed to determine the effects of short-chain fatty acids on the gastrointestinal mucosa and their relationships with diet, fibre, and the gut-brain axis. Methods: This study used a systematic review guided by PRISMA 2020 (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). The literature was searched across three databases: PubMed, EBSCO, and Scopus. The study selection process followed predetermined inclusion and exclusion criteria, and the results of included studies were systematically analyzed. Results: A total of 20 studies were analyzed. Most studies show that SCFAs can protect the gastrointestinal mucosa through a healthy microbiota balance and a proper diet, including a high-fiber diet.  Conclusion: A high-fibre diet can produce SCFAs that regulate metabolic/inflammatory genes, improve intestinal mucosal function, enhance glucagon-like peptide-1 (GLP-1) secretion, improve glycemic/appetite control, and reduce the brain's response to high-calorie foods. It also lowers high-sensitivity C-reactive protein (high-sensitivity C-reactive protein (high-sensitivity C-reactive protein (high-sensitivity C-reactive protein (high-sensitivity C-reactive protein (hs-CRP))))), improving stress, anxiety, and mental health. Contribution to Sustainable Development Goals (SDGs):SDG 3- Good Health and Well-BeingSDG 4:- Quality EducationSDG 12 – Responsible Consumption and Production